Interleukin-1β augments angiogenic responses of murine endothelial progenitor cells in vitro - Rosell, Anna (2009)
Endothelial progenitor cells (EPCs) may provide novel opportunities for therapeutic angiogenesis after ischemic diseases. However, it is unclear how the angiogenic potential of EPCs might be affected by an inflammatory environment. We examine how the potent cytokine interleukin-1β (IL-1β) affects angiovasculogenic responses in EPCs in culture. Mononuclear cells isolated from mouse spleen were plated on fibronectin-coated wells and grown in EGM-2MV media. Endothelial progenitor cells were phenotyped using multiple markers (UEA-Lectin, ac-LDL, CD133, CD34, vWillebrand Factor, Flk-1) and to identify the IL-1 Receptor-I. We quantified cell and colony counts and performed MTT (3-(4,5-dimethylthiazol-2-yl)2,5-diphenyl-tetrazolium bromide) and Matrigel assays, in vitro, under control and IL-1β (10 ng/mL) conditions. Endothelial progenitor cells exposed to IL-1β increased in the number of cells and colonies compared with untreated cells, without any effect on cell metabolic integrity. Furthermore, IL-1β treatment augmented EPC angiogenic function, significantly increasing the number of vessel-like structures in the Matrigel assay. An early phosphorylation of ERK1/2 occurred after IL-1β stimulation, and this pathway was inhibited if IL-1 Receptor-I was blocked. Our results suggest that IL-1β is a potent stimulator of in vitro angiogenesis through ERK signaling in mouse EPCs. Further studies are warranted to assess how interactions between proinflammatory environments and EPC responses may be leveraged to enhance therapeutic angiogenesis.